Edukasi dan Pendampingan Pengembangan Mandu Berbasis Ikan Teri dan Kacang Panjang di Posyandu Kariangau: Education and Capacity Building for the Development of Anchovy- and Long Bean–Based Mandu at Kariangau Community Health Post - Arista, Yuvita; Masyitah, Masyitah; Al Farizie, Adam; Kassang, Adinda Anastasya; Aldona Sabria Wahyudi; Silfiana; Siti Zahra Aulia; Vera Kurniawati; Yuan Reza Sukardi; Yuliana Galuh Ariendra (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2026)
Nutritional problems among children under five, particularly stunting, remain a significant public health challenge associated with inadequate nutrient intake and unfavorable eating behaviors such as picky eating, poor appetite, and feeding difficulties. These conditions may lead to imbalanced macronutrient and micronutrient intake, which adversely affects child growth and development. This Community Service Program (PkM) aimed to improve parental knowledge and skills in fulfilling child nutritional requirements through education and training on innovative food processing based on local ingredients, namely mandu formulated with anchovy (Stolephorus spp.) and yardlong bean (Vigna unguiculata subsp. sesquipedalis). The methods included educational sessions, hands-on training, mentoring, and evaluation using a structured questionnaire. The evaluation involved 18 participants, where 83.3% achieved an excellent category and 16.7% a good category.The practice-based educational approach combined with the utilization of locally available nutrient-dense ingredients was effective in enhancing community capacity and shows potential as a preventive strategy to reduce the risk of stunting at the household level.